Web Based Home Learning Application For Basic School Children - Jansen, Gregorius Ericco; Mogi, I Komang Ari (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 10 No 1 (2021): JELIKU Volume 10 No 1, Agustus 2021, 2021)
Currently, technological developments, especially in the field of information technology and computers, are developing very rapidly. In current conditions, the world is shocked by the presence of a deadly virus called the Covid-19 virus. Because of the virus, all human activities are disrupted and even stopped, one of which is teaching and learning activities in schools. With the development of technology like now, we can take advantage of this technology to help students in the learning process at school. Web design is an alternative way to keep the learning process going. With this distance learning process students can still learn and receive the material given.